Two new species of Tripogon (Poaceae: Chloridoideae: Tripogoninae): from India - Kottekkattu, Thoiba; Manudev, K.m.; Pradeep, A.k. (Phytotaxa, 2016)
Two new species of Poaceae, Tripogon karnatakensis and T. munnarensis from South India are described and illustrated. T. karnatakensis closely resembles T. filiformis, but differs in having 15–28 cm long leaden green spikes with 2-keeled lower glumes. T. munnarensis closely resembles T. narayanae, but differs in having 10–16 mm long spikelets with 10–16 florets.